Komunikasi Keluarga Terhadap Motivasi Belajar Anak Selama Masa Pandemi Covid 19 - Shofiyah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2021)
The case of the COVID 19 pandemic in Indonesia was confirmed on March 2, 2020, and grew so quickly that it expanded to 34 provinces. With the issuance of Circular Letter Number 15 of 2020 concerning "Guidelines for the Implementation of Learning from Home in an Emergency Period for the Spread of COVID-19", the teaching and learning process is carried out remotely (PJJ). ) internet-based. This greatly affects the teaching and learning process in children. Because not all of them can access the internet for various reasons, so it is very influential on children's learning interest. Therefore, the motivation of parents while accompanying children to study at home is very necessary. The function of the family as a madrasa, first and foremost, must be able to provide learning motivation for children, through communication patterns built by parents greatly determine children's learning motivation during a pandemic.